2011
DOI: 10.1534/genetics.110.122390
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the “Popcorn” Wolbachia Infection in Outbred Aedes aegypti Informs Prospects for Mosquito Vector Control

Abstract: Forty percent of the world's population is at risk of contracting dengue virus, which produces dengue fever with a potentially fatal hemorrhagic form. The wMelPop Wolbachia infection of Drosophila melanogaster reduces life span and interferes with viral transmission when introduced into the mosquito Aedes aegypti, the primary vector of dengue virus. Wolbachia has been proposed as an agent for preventing transmission of dengue virus. Population invasion by Wolbachia depends on levels of cytoplasmic incompatibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
231
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(240 citation statements)
references
References 48 publications
6
231
1
2
Order By: Relevance
“…This observation is similar to a prior study of the single wMelPop infection (Suh et al 2009) while the life-shortening effect seemed to be relatively reduced comparing to prior studies of wMelPop-CLA (wMelPop cell line adapted) infection in Ae. aegypti (McMeniman et al 2009, Yeap et al 2011. YFU males, in contrast, experienced an increased life span, relative to naturally infected IH males (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This observation is similar to a prior study of the single wMelPop infection (Suh et al 2009) while the life-shortening effect seemed to be relatively reduced comparing to prior studies of wMelPop-CLA (wMelPop cell line adapted) infection in Ae. aegypti (McMeniman et al 2009, Yeap et al 2011. YFU males, in contrast, experienced an increased life span, relative to naturally infected IH males (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…These observations differ from prior studies in which wMelPop-CLA Wolbachia were observed to reduce embryonic survival in Ae. aegypti (McMeniman et al 2009, Yeap et al 2011. Such differential phenotypic effect could be due to genotypic differences in Wolbachia strains (wMelPop vs. wMelPop-CLA) and different mosquito species, resulting in differential density and tissue tropism of wMelPop in Ae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aegypti because it proliferates throughout the entire mosquito. 11,12,15 The wMelPop infection reduces adult longevity by as much as 50% and decreases egg viability, fecundity, 10,16,17 and blood feeding success of females. 18 Although the costs of wMelPop infection on adult Ae.…”
Section: Introductionmentioning
confidence: 99%